2013
DOI: 10.1021/ic3023776
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cation Interactions in the Reduction Process in Plutonium–Americium Mixed Oxides

Abstract: The oxygen to metal ratio (O/M) is directly related to oxygen potential, which strongly influences the sintering and irradiation performance of nuclear fuels. A better understanding of these two parameters is therefore of major interest. To further ascertain the correlation between O/M ratio and oxygen potential in Am-bearing MOX, several thermodynamic descriptions are being developed. Despite their differences, they all involve the valence of actinide cations (e.g., U, Pu, and Am) as essential parameters. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 31 publications
7
34
0
Order By: Relevance
“…As an illustration, a previous study shown that PuF 3 results are identical to those obtained for (U(IV),Pu(III)) mixed oxalates [35]. The latter being a similar system to that of the current study, the use of PuF 3 as the Pu(III) reference is thus adequate.…”
Section: Apparatus and Experimental Techniquessupporting
confidence: 78%
See 3 more Smart Citations
“…As an illustration, a previous study shown that PuF 3 results are identical to those obtained for (U(IV),Pu(III)) mixed oxalates [35]. The latter being a similar system to that of the current study, the use of PuF 3 as the Pu(III) reference is thus adequate.…”
Section: Apparatus and Experimental Techniquessupporting
confidence: 78%
“…The position of white line maximum was determined by the first zero-crossing of the first derivative. UO 2 , U 4 O 9 , U 3 O 8 , PuO 2 and PuF 3 were used as references for the oxidation states of the uranium [29,31,32] and plutonium [29,[33][34][35] cations, respectively. Although the empty density of state probed by XANES is different between PuF 3 and plutonium oxides, the core-hole lifetime (8.7 eV) at…”
Section: Apparatus and Experimental Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently, Belin et al [26] measured the Pu and Am valences in (Pu 1-y Am y )O 2-x by X-ray absorption near edge structure (XANES) and proved that Pu reduction from Pu 4 + to Pu 3 + started after all Am was reduced. Therefore, this model was reasonably adopted to analyze the Ḡ o 2 using the point defect chemistry.…”
Section: Analysis Based On the Point Defect Chemistrymentioning
confidence: 99%